2021
DOI: 10.9734/jpri/2021/v33i47b33121
|View full text |Cite
|
Sign up to set email alerts
|

Overview on Causes and Updated Management of Favism

Abstract: Favism is most common in those who have G6PD deficiency from the Mediterranean region. As hemolytic anaemia is the most common complication of G6PD deficiency, and it can be life-threatening in certain people. Infection, hyperglycemia, certain meals, and certain drugs can all cause hemolysis therefore, the most prevalent enzymopathy is glucose-6-phosphate dehydrogenase (G6PD) deficiency, which affects an estimated 400 million individuals, globally. Exposure to some medicines might cause hemolytic anaemia. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In addition to meeting or exceeding dietary requirements for all essential minerals except calcium (AEGIC, 2021), they contain relatively high levels of beneficial antioxidant and phenolic compounds, which may provide protection against reactive oxygen species, as well as anti‐hypertensive and anti‐cancer effects (Martineau‐Côté, Achouri, Karboune, et al, 2022; Martineau‐Côté, Achouri, Wanasundara, et al, 2022; Siah et al, 2012; Turco et al, 2016). However, the presence of anti‐nutritional factors, principally the pyrimidine glycosides vicine and convicine, can also negatively impact on the health benefits associated with this crop (Duc et al, 1999; Khazaei et al, 2019; Wang & Ueberschär, 1990) and cause haemolytic anaemia in individuals with favism (Cappellini & Fiorelli, 2008; Pulkkinen et al, 2016; Sheikh et al, 2021). Consequently, there is a widespread need for closely monitoring the levels of both health‐benefitting and anti‐nutritive compounds in faba bean.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to meeting or exceeding dietary requirements for all essential minerals except calcium (AEGIC, 2021), they contain relatively high levels of beneficial antioxidant and phenolic compounds, which may provide protection against reactive oxygen species, as well as anti‐hypertensive and anti‐cancer effects (Martineau‐Côté, Achouri, Karboune, et al, 2022; Martineau‐Côté, Achouri, Wanasundara, et al, 2022; Siah et al, 2012; Turco et al, 2016). However, the presence of anti‐nutritional factors, principally the pyrimidine glycosides vicine and convicine, can also negatively impact on the health benefits associated with this crop (Duc et al, 1999; Khazaei et al, 2019; Wang & Ueberschär, 1990) and cause haemolytic anaemia in individuals with favism (Cappellini & Fiorelli, 2008; Pulkkinen et al, 2016; Sheikh et al, 2021). Consequently, there is a widespread need for closely monitoring the levels of both health‐benefitting and anti‐nutritive compounds in faba bean.…”
Section: Introductionmentioning
confidence: 99%
“…G6PD was first discovered in horse erythrocytes in 1931 by Warburg and Christian 5 . According to the World Health Organization G6PD Deficiency Working Group (WHO-G6PD) criteria (biochemical, kinetic, clinical), over 400 G6PD variants have been identified 6,7 . According to the screening studies conducted in the Çukurova region, the rate of G6PD deficiency was reported to be 8.2% 8 .…”
Section: Introductionmentioning
confidence: 99%